THE HEALTH PROMOTION OF CARDIOVASCULAR DISEASE PREVENTION BY COMMUNITY HEALTH NURSE IN PRIMARY HEALTH CARE: A SYSTEMATIC REVIEW - Rizkiyani Istifada; Etty Rekawati (International Journal of Nursing and Health Services (IJNHS), 2019)
Health promotion is a method to increase awareness of healthy behavior in public. Unhealthy lifestyles cause increases the risk of cardiovascular disease. Community health nurses have a responsibility to increase the motivation of healthy practice with the health promotion’s method. This research method used a systematic review, using online databases on Cambridge Core, Wiley Online, and Science Direct e-resources when the articles published from 2006-2018. The selection of literature used the Critical Capability Program (CASP) tool and got eight relevant articles. The systematic analysis used the Cochrane Collaboration. The themes of this article are 1) nurses’ knowledge about health promotion, 2) the meaning of health promotion, and 3) the implementation health promotion of cardiovascular disease prevention by nurses. The themes identified some categories, such as nurse responsibilities, the essence of health promotion, support and barriers, and health promotion’s method. The nurse’s perception of health promotion is the core of their work to decrease the prevalence of the cardiovascular disease. Keywords: cardiovascular disease, health promotion, nurses, primary health care